Measurement of singlet delta oxygen in an atmospheric-pressure helium–oxygen plasma jet. (5th May 2017) - Inoue, Yuki; Ono, Ryo
Abstract: The density of singlet delta oxygen O 2 ( a 1 Δ g ) is measured in situ in a He/O2 atmospheric-pressure plasma jet using optical emission spectroscopy at 1.27 μ m. A sinusoidal high voltage of 1–10 kHz is applied between two electrodes wrapped around a quartz tube, in which the working gas flows. The two-dimensional distribution of the O 2 ( a 1 Δ g ) density shows that O 2 ( a 1 Δ g ) is primarily produced in the dielectric barrier discharge inside the quartz tube and that the O 2 ( a 1 Δ g ) production in the plasma jet plume is negligibly small. Typically, 100 ppm of O 2 ( a 1 Δ g ) is produced. The O 2 ( a 1 Δ g ) density increases with O2 concentration and is proportional to the specific input energy (SIE; J/l) irrespective of the discharge voltage, frequency, and gas flow rate. The O 2 ( a 1 Δ g ) production per SIE was 10 ppm/(J/l). The loss processes of O 2 ( a 1 Δ g ) via reactions with O3 and O2 are discussed. The O 2 ( a 1 Δ g ) density decreases when the working gas is humidified. An addition of 200 ppm of H2 O decreases the O 2 ( a 1 Δ g ) density by half.